2013
DOI: 10.1051/0004-6361/201321826
|View full text |Cite
|
Sign up to set email alerts
|

Structure of solar coronal loops: from miniature to large-scale

Abstract: Aims. We use new data from the High-resolution Coronal Imager (Hi-C) with its unprecedented spatial resolution of the solar corona to investigate the structure of coronal loops down to 0.2 . Methods. During a rocket flight, Hi-C provided images of the solar corona in a wavelength band around 193 Å that is dominated by emission from Fe  showing plasma at temperatures around 1.5 MK. We analyze part of the Hi-C field-of-view to study the smallest coronal loops observed so far and search for the possible substr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
127
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(155 citation statements)
references
References 47 publications
(64 reference statements)
25
127
0
3
Order By: Relevance
“…Loops in the model match observations in terms of diameter, or cross section [68,102]. In general, loop structures found in observations, such as thin or thick loops at constant cross section, or expanding envelopes of several thin loops, are also seen in the three-dimensional MHD models [103]. A three-dimensional MHD model that was run to match an actual observation did even reproduce the location of a set of loops in three-dimensional space, as revealed by a comparison to stereoscopic observations [48].…”
Section: (A) Synthetic Observationssupporting
confidence: 56%
“…Loops in the model match observations in terms of diameter, or cross section [68,102]. In general, loop structures found in observations, such as thin or thick loops at constant cross section, or expanding envelopes of several thin loops, are also seen in the three-dimensional MHD models [103]. A three-dimensional MHD model that was run to match an actual observation did even reproduce the location of a set of loops in three-dimensional space, as revealed by a comparison to stereoscopic observations [48].…”
Section: (A) Synthetic Observationssupporting
confidence: 56%
“…1; alternatively, one may state that a diameter of 0. 1 represents an upper limit for the strands which make up an observed loop Peter et al 2013).…”
Section: Coronal Loopsmentioning
confidence: 99%
“…Consequently, our observation supports that the tether-cutting of magnetic loops occurred before the filament eruption. The coronal loops may be composed of many strands (Peter et al 2013). In this event, we observed that the bright loop split into several strands.…”
Section: Conclusion and Discussionmentioning
confidence: 64%
“…Priest et al 1989;Rust & Kumar 1994;Amari et al 1999;Gibson & Fan 2006). Van Ballegooijen & Martens (1989) and Aulanier et al (2010) proposed that shearing and converging footpoint motions will force magnetic reconnection between the arcade field lines, progressively transforming the arcade magnetic field lines into a twisted flux tube.…”
Section: Introductionmentioning
confidence: 99%